Social Media as a Medium for Participation in the ‘Kupu-Kupu’ Student Social Movement at UIN Jakarta: Activism Without Street Demonstrations - Faiz Fattan Nasution; Kayla Putri Ramadhani; Lois Anatasia Arden; Samuel Frans Tinambunan Frans Tinambunan; Wahyuningsih Subekti (UMSU, 2026)
This study aims to understand how “butterfly students”students whose daily activities are limited to attending lectures and going straight home develop political awareness and social empathy toward student social movements through social media, particularly during the demonstration occurring on 25–28 August 2025. Using a qualitative approach with descriptive phenomenology based on Clark Moustakas’ framework, this research explores the lived experiences of students who did not directly participate in the protest. Participants consisted of students from the State Islamic University, and data were collected through semi-structured online in-depth interviews. The analysis followed the stages of epoche, phenomenological reduction, meaning units, imaginative variation, and synthesis of essence. The findings reveal that butterfly students experience fear and concern toward physical demonstrations, yet they still construct passive empathy and reflective political awareness through their digital interactions on social media. These results indicate that butterfly students are not entirely apathetic; rather, they demonstrate a reflective form of participation that remains relevant within the context of digital democracy.